Perspectives and Management of Atypical Asthma in Chinese Specialists and Primary Care Practitioners—A Nationwide Questionnaire Survey - Huang, Huaqiong; Hua, Wen; Chen, Ruchong; Hu, Yue; Ying, Songmin; Chi, Chunhua; Zhang, Min; Huang, Kewu; Liu, Huiguo; Shen, Huahao; Lai, Kefang (Frontiers in Medicine, 2021)
Background and objective: To evaluate the awareness/knowledge and clinical practice for the treatment of atypical asthma among respiratory specialists and primary care practitioners (PCPs) in China. Methods: A total of 1997 physicians participated in the questionnaire via WeChat. The questionnaire included six main items: physician demographic characteristics, awareness, diagnosis, medical prescription, assessment/education, and proposal. Results: Cough variant asthma (CVA) was recognized by 97.51% of physicians(1166 respiratory specialists and 799 PCPs), followed by chest tightness variant asthma (CTVA, 83.72%) and occult asthma (73.54%). Specialists were more likely to follow diagnostic recommendations than PCPs (P<0.01); however, 34.15% of physicians reported the utility of bronchodilation tests, airway provocation tests, and peak expiratory flow monitoring. A total of 91.70% and 92.01% of physicians prescribed inhaled corticosteroids (ICS) or ICS plus long-acting beta-agonists (LABA) for CVA and CTVA, respectively. Physicians prescribed an ICS or ICS/LABA for 4 [2-8] or 8 [4-12] weeks for CVA and 4 [2-8] or 5 [4-12] weeks for CTVA, and the prescription durations were significantly shorter for PCPs than for specialists (P<0.01). Further, 52.42% and 35.78% reported good control of CVA and CTVA, respectively, with significantly lower control rates for PCPs than for specialists (P<0.01). Additionally, specialists exhibited better assessment and educational habits than PCPs. Conclusion: While atypical asthma was identified by most specialists and PCPs, there remains a gap between management in real clinical practice and guideline recommendations, especially for PCPs. Further training of PCPs and clinical studies of atypical asthma are required to better improve outcomes.